(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Modern principles of ion radiation and physical foundations of MSCT Multislice spiral computed tomography (MSCT) is one of the most advanced technologies in modern X-ray diagnostics, providing high spatial and temporal resolution while minimizing radiation exposure to the patient. MSCT utilizes the spiral (or conical-spiral) motion of the X-ray tube around the patient’s body, while simultaneously moving the table forward, allowing for continuous tomographic data acquisition across the entire volume being examined.